Elemental Analysis of Ochre Outcrops in Southern British Columbia, Canada. (16th October 2012) - Macdonald, B. L.; Hancock, R. G. V.; Cannon, A.; McNeill, F.; Reimer, R.; Pidruczny, A.
<x xml:space="preserve">Abstract</x> Ochre is a red mineral pigment that was a key element of social and ceremonial practices among cultures of the Pacific Northwest Coast. It is recovered routinely from archaeological excavations, is visible as pigment for pictographs, and is described in the historical record as a trade item and component of ceremonial practices. Despite its ubiquity in the archaeological record, it is difficult to interpret its significance without first understanding the nature of its procurement and distribution. As a step towards identifying procurement practices, trade and resource use, it is necessary to thoroughly characterize ochre outcrops with regard to their intra‐source and regional variability. We analysed ochre from three outcrops using INAA to determine their elemental chemistry. The purpose of this study is threefold: to provide an example of the range of elemental variability within and between outcrops, to illustrate the effect of scale and geomorphological processes on elemental compositions and statistical interpretation, and to create a database of known deposits in southern British Columbia. The results demonstrate that ochre deposits may be differentiated on the basis of their chemistry, and that conservative statistical interpretation needs to be employed to assess true elemental variability within and between ochre deposits and regions.